2013
DOI: 10.1111/ajt.12434
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Kidney Donors From the Last Five Decades: Results From the RELIVE Study

Abstract: Live donation benefits recipients, but the long-term consequences for donors remain uncertain. RELIVE surveyed kidney donors (N=2,455; 61% women; mean age 58, aged 24 – 94; mean time from donation 17 years, range 5 – 48 years) using the SF-36. The 95% CIs for white and African-American donors included or exceeded SF-36 norms. Over 80% of donors reported average or above average health for their age and sex (p<0.0001). Donors’ age-sex adjusted physical component summary [PCS] scores declined by half a point eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
86
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 27 publications
9
86
2
2
Order By: Relevance
“…In one study, potential donors who were overweight or obese, less educated, had prior psychiatric difficulties, were not white, or not first-degree relatives of the recipient represented groups at risk for poor HRQOL. New or enhanced efforts of predonation counseling and education, particularly weight loss counseling and post-donation monitoring efforts, could improve outcomes of these donors (30). Consistent with the exiting literature, our work showed that there was no significant difference in terms of the quality of life when donor candidates were grouped by degree of affinity, on the other hand, the quality of life-pain subscale score was higher for kidney donor candidates.…”
Section: Discussionsupporting
confidence: 86%
“…In one study, potential donors who were overweight or obese, less educated, had prior psychiatric difficulties, were not white, or not first-degree relatives of the recipient represented groups at risk for poor HRQOL. New or enhanced efforts of predonation counseling and education, particularly weight loss counseling and post-donation monitoring efforts, could improve outcomes of these donors (30). Consistent with the exiting literature, our work showed that there was no significant difference in terms of the quality of life when donor candidates were grouped by degree of affinity, on the other hand, the quality of life-pain subscale score was higher for kidney donor candidates.…”
Section: Discussionsupporting
confidence: 86%
“…It is considered a procedure with low morbidity and mortality rates [20,21]. Health-related quality of life (HRQoL) of LKD is an important topic which has been investigated in several studies [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Although the risks of gestational hypertension and pre-eclampsia seem to be higher in pregnancies among donors than among healthy Work exploring the mental health of living kidney donors is limited, but a recent case-control study from the Netherlands suggested that donation is not associated with short term changes in mental health. 64 Multiple studies suggest that the quality of life of most living kidney donors seems to be at least equal to that of the general population [65][66][67][68][69][70][71][72] and usually returns to pre-donation levels after donation. A thematic synthesis of qualitative work from Europe, the United States, Canada and Australia, however, identified some negative donation-specific experiences among the overall positive experiences, including a sense of loss, fear, vulnerability, and neglect.…”
Section: Advising Donors About Risksmentioning
confidence: 99%